2017
DOI: 10.1103/physrevlett.118.073001
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Dynamics of a Superradiant Quantum Phase Transition with a Single Trapped Ion

Abstract: We demonstrate that the quantum phase transition (QPT) of the Rabi model and critical dynamics near the QPT can be probed in the setup of a single trapped ion. We first show that there exists equilibrium and nonequilibrium universal functions of the Rabi model by finding a proper rescaling of the system parameters and observables. We then propose a scheme that can faithfully realize the Rabi model in the limit of a large ratio of the effective atomic transition frequency to the oscillator frequency using a sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 50 publications
(94 reference statements)
1
114
0
Order By: Relevance
“…From a theoretical point of view, our work justifies further research in light-matter coupling regimes that are a priori not found in nature, as we are providing a platform where all these regimes can be physically implemented. Our experimental methods can be directly extended to the study of the phase transition in the QRM [49][50][51] or to the simulation of the Dicke model [52][53][54] by considering the presence of more ions. configuration, we obtain the resonance frequency of the red-sideband transition with the detuning of the bluesideband transition fixed at ÎŽ b ÂŒ Ă°2Ï€Ăž625 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…From a theoretical point of view, our work justifies further research in light-matter coupling regimes that are a priori not found in nature, as we are providing a platform where all these regimes can be physically implemented. Our experimental methods can be directly extended to the study of the phase transition in the QRM [49][50][51] or to the simulation of the Dicke model [52][53][54] by considering the presence of more ions. configuration, we obtain the resonance frequency of the red-sideband transition with the detuning of the bluesideband transition fixed at ÎŽ b ÂŒ Ă°2Ï€Ăž625 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the QRM has been exhaustively investigated in the last decades, a number of recent findings has brought it again into the research spotlight. Among them we can mention its integrability [13], the existence of a distinctive behaviour in the deep strong coupling regime [14], or the emergence of a quantum phase transition [15][16][17][18]. Closely related to the QRM, we find the nth order QRM (nQRM) which differs from the QRM in that the nQRM comprises n-boson exchange interaction terms because of the presence of a nonlinear spinboson coupling.…”
Section: Introductionmentioning
confidence: 93%
“…IV F, it is possible to extract such an equation from the general dissipators we construct in PIQS. (Though this procedure is not strictly necessary in systems where the coupling is only "effectively" strong, and where the bare-basis master equation is still valid [28,29,78,[99][100][101][102][103][104][105][106][107]).…”
Section: Theorymentioning
confidence: 99%